Punishment Strategies: First Choice or Last Resort - Lukowiak, Twila; Bridges, Jennifer (Journal of the American Academy of Special Education Professionals, 2010)
Is it appropriate to implement punishment strategies in the home and school settings when children display disrespectful and inappropriate behaviors? This article depicts the advantages and disadvantages of teachers and parents utilizing an array of punishment strategies including: (a) reprimands, (b) response cost, (c) timeout, and (d) corporal punishment. It is critical that educators and parents know the advantages and disadvantages of each of the punishment strategies so that they can make well informed, knowledgeable decisions.